Depiction of Yama - Temples of India Project Team (Jio Institute, 2024)
Yama, the guardian of the southern realm, stands with an air of solemnity and grace. Despite the loss of his upper right hand, which once held the danda (rod of justice), his presence remains commanding. In his upper left hand, he holds a rooster. His lower left hand holds a kamandalu (water pot), and his lower right-hand holds a rosary and makes a varada hasta (boon-giving gesture). Crowned and adorned with jewels, Yama is accompanied by his mount, the buffalo.